Science Communication of Brazilian Software Engineering Research on LinkedIn - Garcia, Luiza Carolina Miranda; Herpich, Fabricio; Souza, Cleidson R. B. de; Bordin, Andréa Sabedra (Anais do Simpósio Brasileiro de Engenharia de Software (SBES), 2025)
This study investigates how Brazilian Software Engineering Research is communicated on LinkedIn, a professional social network, by analyzing the characteristics of posts, the profile of communicators and the interactions received by posts. We used web scraping and manual classification techniques to collect, extract and process attributes related to the content of posts, authors, and interactions. A total of 336 posts referring to scientific software engineering conferences (SBES, SBQS, CIBSE, and ICSE) were extracted and analyzed, and 172 were identified as being related to science communication. Our results suggest that science communication is predominantly carried out by individual profiles, with a greater frequency of industry professionals, with self-promotion being the main goal of the posts analyzed. We also observed extensive use of visual resources and the limited use of scientific elements that facilitate the understanding of research, such as methodologies and research results. These findings suggest that, although LinkedIn can broaden the reach of science communication, this still requires further improvement. Accordingly, we present recommendations to make scientific content more accessible, effective and engaging on LinkedIn.